Pemanfaatan Potensi Tanaman Mawar Melalui Pelatihan Ecoprint Oleh Kelompok KKN 192 UIN Sunan Kalijaga Yogyakarta Di Desa Sruni, Musuk, Boyolali - Fahmi Hadianto; Brilliant Deanova; Ridwan Abdillah; Luluk Shomitah; Hani Wahyuningsih; Muhammad Husnul ‘Abid; Syafira Rahma Auliani; Dea Fika Nabila; Syifani Annisa Fitria (Yayasan Pemimpin Inovasi Science, 2025)
Ecoprint is a fabric dyeing or motif printing technique using natural materials as the main ingredient. Ecoprint technique was introduced to PKK ladies in Sruni Village considering that rose plants are plants that are always found in the homes of Sruni Village residents. This article discusses efforts to utilise the potential of rose plants in Sruni Village, Boyolali through ecoprint training conducted by KKN 192 Batch 114 UIN Sunan Kalijaga Yogyakarta. This training aims to provide knowledge and skills to the people of Sruni Village in utilising rose plants as ecoprint raw materials, so as to increase the economic value of rose plants and open new business opportunities. The method used in this research is a hands-on method with a participatory approach. Data were collected through observation, direct participation, interviews, and documentation. The results showed that the ecoprint training was able to increase the knowledge and skills of the Sruni Village community in processing rose plants into ecoprint products with economic value. In addition, this training was able to raise awareness of the importance of utilising the potential of the surrounding nature optimally and efficiently.